INFLEKSI BAHASA MELAYU RIAU DIALEK KUANTAN SINGINGI KECAMATAN GUNUNG TOAR - Anggriani Safitri; Auzar '; Hasnah Faizah AR (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study discusses the process of word formation inflection inflection and meaning of words contained in the language of the Malay dialect Singingi Kuantan District of Mount Toar. This study aimed to describe the process of word formation inflection and change the meaning of words as a result of the process of inflection in the language of the Malay dialect Singingi Kuantan District of Mount Toar. Helpful research theoretically and practically. This study is a qualitative research and descriptive method. Techniques used in data collection in this research that recording technique and technique refer to note. The data that has been discovered and analyzed by several stages, ie transcribing the data, rewriting the data obtained, classifying the data, analyze the data, and write the results of the analysis. Data sourced words found inflections of speech and folklore where the study was conducted. The object of this study is the language. The results of this study as a contribution for further research regarding inflection.Keywords: Inflection, Language Melayu Riau, Kuantan Singingi.